2022
DOI: 10.1186/s12964-022-00828-0
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial colony-forming cell-derived exosomal miR-21-5p regulates autophagic flux to promote vascular endothelial repair by inhibiting SIPL1A2 in atherosclerosis

Abstract: Background Percutaneous transluminal coronary angioplasty (PTCA) represents an efficient therapeutic method for atherosclerosis but conveys a risk of causing restenosis. Endothelial colony-forming cell-derived exosomes (ECFC-exosomes) are important mediators during vascular repair. This study aimed to investigate the therapeutic effects of ECFC-exosomes in a rat model of atherosclerosis and to explore the molecular mechanisms underlying the ECFC-exosome-mediated effects on ox-LDL-induced endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Our previous investigation revealed that ECFCs are an important angiogenic mediator involved in DO [ 29 ]. It was confirmed that ECFCs-derived exosomes serve as important mediators during vascular repair and angiogenesis [ 30 , 31 ]. Several reports raised the possibility that ECFCs do not directly incorporate into newly developed vasculature, instead they stimulate the proliferation and migration of tissue-resident endothelial cells (ECs), using paracrine networks [ [32] , [33] , [34] ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous investigation revealed that ECFCs are an important angiogenic mediator involved in DO [ 29 ]. It was confirmed that ECFCs-derived exosomes serve as important mediators during vascular repair and angiogenesis [ 30 , 31 ]. Several reports raised the possibility that ECFCs do not directly incorporate into newly developed vasculature, instead they stimulate the proliferation and migration of tissue-resident endothelial cells (ECs), using paracrine networks [ [32] , [33] , [34] ].…”
Section: Discussionmentioning
confidence: 99%
“…And recent omics-based studies on normal vs. CAVD tissues built molecular interaction networks and the key factors and disease association were identi ed 22,25 . Previous studies have MiR-21-5p has been identi ed as a key regulator in chronic heart failure and atherosclerosis 12,13 , which implied the role of miR-21-5p in cardiovascular diseases. Additionally, miR-21-5p has been reported to regulate extracellular matrix degradation and angiogenesis of condylar chondrocytes in temporomandibular joint osteoarthritis, which suggested miR-21-5p involving in osteogenic pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, the important roles of miRNAs in diagnosis and treatment of cardiovascular diseases, including atherosclerosis, hear failure, cardiac hypertrophy and so on, were revealed in numerous research [9][10][11] . In particular, miR-21-5p has been recently validated its role in chronic heart failure 12 and atherosclerosis 13 . Additionally, miR-21-5p was identi ed as key factor in pathological mechanism of temporomandibular joint osteoarthritis mediated by its action on extracellular matrix degradation and angiogenesis 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the studies described above, two recent studies have suggested the therapeutic potential of exosomes. Ke et al suggested that endothelial colony-forming cell-derived exosomes regulate lipid homeostasis, activate autophagy, attenuate vascular endothelial injury, and play a protective role in AS [ 90 ]. Zhang et al reported that mesenchymal stem cell-derived exosomes fight against damaged ECs induced by ox-LDL and restore vascular activity by fetal-lethal non-coding developmental regulatory RNA [ 91 ].…”
Section: Discussionmentioning
confidence: 99%